Russia's war on Ukraine, European energy policy responses & implications for sustainable transformations. (November 2022) - Kuzemko, Caroline; Blondeel, Mathieu; Dupont, Claire; Brisbois, Marie Claire
Abstract: Russia's February 2022 invasion of Ukraine sent shockwaves throughout Europe and has painfully exposed the continent's dependence on a geopolitical adversary. Energy is closely tied into the ongoing battle: Europe is committed to phasing out Russian fossil fuel imports, whilst Russia, in turn, has cut gas supplies to a number of countries and significantly reduced flows to others. Given historical tensions between delivering supply security and other social goals we analyse what energy policy responses to the crisis so far mean for: environmental sustainability, energy equity and social justice. In doing so, we reveal strong potential for an acceleration of clean energy supply across Europe, complications for fossil fuel phase out, negative knock-on effects for sustainable transitions in the Global South, significant implications for energy equity within and beyond Europe, and a relative return of the state as an energy actor. Reframing energy as a geopolitical security concern has, in acute crisis, tended to obfuscate and/or downplay other energy policy goals, raising a number of difficult questions for policymakers seeking to pursue lasting sustainable and equitable transitions.